96.6k views
3 votes
5x-6=3x-8
A.-1
b.-6
c.-9
d.33

2 Answers

4 votes

Answer:

A: -1

Explanation:

And the other person did a really good job at explaining it :)

User Mansur Khan
by
4.2k points
4 votes

Answer:

A. - 1

Explanation:

5x - 6 = 3x - 8

Then, Please add Six, to both sides.

5x - 6 + 6 =3x - 8 + 6

Then, You need to simplify.

5x = 3x - 2

Then, Subtract the 3x from all sides.

5x - 3x = 3x - 2 - 3x

Then, You need to simplify again.

2x = - 2

Then, Divide all sides by, 2.

2x/2 = -2/2

Then, Simplify again to get, your answer!

X = -1

User VirtualValentin
by
5.3k points